Five-Stranded Hamstring Tendon Autograft for Anterior Cruciate Ligament Reconstruction - Anthony Zacharias MD; Geoffrey Baer MD, PhD (SAGE Publishing, 2022)
Background: Hamstring tendon (HT) autograft for anterior cruciate ligament (ACL) reconstruction has shown equivalent graft failure rates to bone-patellar-tendon-bone (BTB) with decreased prevalence of anterior knee pain. It should be noted that young athletes, particularly females athletes, may have increased graft failure rates with HT versus BTB. Additionally, HT graft diameters <8 mm have shown worse patient-reported outcomes and higher graft failure rates. Five-strand HT autograft offers a method to increase graft size without utilization of allograft tissue or synthetic material. Indications: This presentation describes the technique for 5-strand HT autograft reconstruction of the ACL. Tips and tricks on graft prep, tunnel placement, tunnel depth, and avoiding pitfalls in surgery are provided. Technique Description: Gracilis and semitendinosus tendon harvest is performed through an L-shaped flap of sartorial fascia. If the 4-strand configuration is <8 mm, the semitendinosus is tripled for a 5-strand configuration. Graft is attached to a 15-mm fixed-length button construct for femoral fixation. The tibial tunnel is typically drilled with the guide through the accessory anteromedial portal. Independent femoral tunnel drilling is then performed via the accessory anteromedial tunnel with the knee in hyperflexion, using an offset guide to aid in tunnel placement. Femoral tunnel is initially reamed to depth of 25 mm and then drilled through the far cortex with a 4.5-mm drill to allow for suspensory fixation. Total length to the lateral cortex is measured and reaming of the tunnel is performed to achieve a 5- to 7-mm difference between total tunnel length to the lateral cortex and reamed tunnel length, assuring room for the button to flip on the femoral cortex. Tibial fixation is achieved by interference fixation versus tying the free suture limbs over a post with a washer. Results: Recent studies show the HT autograft to have similar re-rupture rates for ACL reconstruction compared with other autograft options. Additionally, this option has low donor-site morbidity and has demonstrated significant less anterior knee pain and kneeling pain postoperatively. Discussion/Conclusion: ACL reconstruction with 5-strand HT autograft has shown to be an effective method to increase the graft diameter with low rates of donor-site morbidity.